2016
DOI: 10.1007/s10853-016-0053-y
|View full text |Cite
|
Sign up to set email alerts
|

The usability of recycled carbon fibres in short fibre thermoplastics: interfacial properties

Abstract: The objective of this study was to investigate the feasibility of combining discontinuous recycled carbon fibres with polypropylene, to produce a low-cost, high specific stiffness material for high-volume applications. The inherent low affinity of carbon fibre and polypropylene motivated a detailed study of the surface characteristics of carbon fibre and interfacial behaviour between the two materials, using the microbond test. The effects of removing the sizing from the fibres, as well as introducing a maleic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 60 publications
(79 reference statements)
2
24
0
Order By: Relevance
“…The CF.EP fracture sites were significantly different to those of the CF.PP and CF.mPP composites, with no flexibility in the exposed tows, confirming excellent adhesion between fibre and matrix. This supports the observations from the microdroplet testing [12], which confirmed that the interfacial shear strength of CF.PP improves with the addition of 2wt%. mPP, but the resulting interface is still weaker than that of the carbon fibre epoxy.…”
Section: 1supporting
confidence: 90%
See 4 more Smart Citations
“…The CF.EP fracture sites were significantly different to those of the CF.PP and CF.mPP composites, with no flexibility in the exposed tows, confirming excellent adhesion between fibre and matrix. This supports the observations from the microdroplet testing [12], which confirmed that the interfacial shear strength of CF.PP improves with the addition of 2wt%. mPP, but the resulting interface is still weaker than that of the carbon fibre epoxy.…”
Section: 1supporting
confidence: 90%
“…Interfacial adhesion can be significantly improved by adding a coupling agent and removing the epoxy-compatible sizing from the carbon, as demonstrated in a previous study by the authors [12].…”
Section: Introductionmentioning
confidence: 67%
See 3 more Smart Citations